Labor markets and labor market institutions in transition economies - Lehmann, Hartmut; Muravyev, Alexander (Bonn, 2011)
"This paper summarizes the evolution of labor markets and labor market institutions and policies in the countries of Central and Eastern Europe as well as of Central Asia over the last two decades. The main focus is on the evolution of labor market institutions, which are among candidate explanations for the very diverse trajectories of labor markets in the region. We consider recent contributions that attempt to assess the effect of labor market institutions on labor market performance of TEs, including the policy-relevant issue of complementarity of institutions."